15N and ²H Intrinsic Labeling Demonstrate That Real Digestibility in Rats of Proteins and Amino Acids from Sunflower Protein Isolate Is Almost as High as That of Goat Whey. Issue 3 (11th December 2019) - Tessier, Romain; Khodorova, Nadezda; Calvez, Juliane; Kapel, Romain; Quinsac, Alain; Piedcoq, Julien; Tomé, Daniel; Gaudichon, Claire
ABSTRACT: Background: In the context of developing plant protein sources for humans, sunflower is a good candidate in its form as an oilseed coproduct. Objectives: We aimed to compare the real digestibility in rats of a sunflower isolate to that of goat whey protein. We also studied the efficiency of 15 N and 2 H intrinsic labeling in this assessment. Methods: Sunflower seeds and goat milk were labeled with 15 N and 2 H. Male Wistar rats (10 wk old) were fed a meal containing 12% of either sunflower isolate ( n  = 8) or whey ( n  = 8). Six hours after meal ingestion, protein and amino acid digestibility were assessed by measuring nitrogen, hydrogen, and amino acids in the digesta, as well as isotope enrichments in the bulk and individual amino acids. The differences between groups and isotopes were respectively tested with an unpaired and a paired t test. Results: Protein isolate purity was 87% for whey and 94% for sunflower. 2 H and 15 N enrichments were, respectively, 0.12 atom % (AP) and 1.06 AP in sunflower isolate and 0.18 AP and 0.95 AP in whey. Fecal 15 N protein digestibility was 97.2 ± 0.2% for whey and 95.1 ± 0.5% for sunflower isolate. The use of 2 H resulted in a lower digestibility estimate than 15 N for whey (96.9 ± 0.2%, P < 0.05) and sunflower (94.2 ± 0.5%, P < 0.01). For both isotopes, protein digestibility was about 2% higher for whey than for sunflower isolate. Mean 15 N amino acid caecal digestibility was 97.5 ± 0.2% for whey and 96.3 ± 0.2% for sunflower isolate. The values obtained with 15 N and 2 H resulted in significant differences ranging from −0.1% to 3.5%. The DIAAS was >1.0 for whey and 0.84 for sunflower (lysine). Conclusions: The protein and amino acid digestibility of sunflower isolate was high but its DIAAS reflected a moderate lysine imbalance. Despite slight differences with 15 N, deuterium produced comparable results, making it suitable for in vivo digestion studies.